The Role of Computerized Accounting information systems in the quality of financial performance Case study of the Ministry of Finance -Sinnar State: دراسة حالة وزارة المالية - ولاية سنار - د. أحمد يوسف مولود إسماعيل,; أ. فاطمة عوض عبد الله, (White Nile Journal for Studies and Research, 2024)
The problem of the study was whether there is a relationship between (the suitability and reliability of accounting information) and the presence of financial effectiveness. The aim of the study was to know the relationship between (the suitability and reliability of computerized accounting information) and the presence of financial performance, and the importance of the study to use the current time to use the information system because this reliable method provides Data and speed at the end, and the use of the Statistical Analysis Program for Social Sciences (SPSS) for statistical analysis and processing. The most important results: that accounting information acquires an almost high quality of financial performance. The most important advice: accounting information and entering the appropriate time helps increase the quality of financial performance. Keywords: Accounting information, Computerized information, financial performance